Utilization of numerical techniques to predict the thermal behavior of wood column subjected to fire part C: Sensitivity analysis - Elshayeb M.; Malik A.R.A.; Ideris F.; Hari Z.; Razak N.A.; Siang J.E.L.; Anuar Z. (Trans Tech Publications Ltd, 2023)
Theoretical studies have been carried out to predict the fire resistance of different configuration of wood columns as done in Part A and Part B of this set of research papers. This theoretical study is a continuation of previous studies, which were carried out at National Research Council Canada. Mathematical models to calculate the temperatures, deformations and fire resistance of the columns have been developed for Part A and Part B. Calculated results are compared with those measured in several tests. The results indicated that the model is capable of predicting the fire resistance of wood columns with an excellent accuracy. By using the model, the fire resistance of wood columns can be evaluated for any value of the significant parameters such as load, physical dimensions, mechanical properties and even the chemical properties without the necessity of experiment. This research paper carried out sensitivity analysis of a square column at elevated temperature in order to know the effect of some parameters towards the mechanical strength of the column. The parameters that have been studied are initial moisture content, Young's modulus, initial compression stress, specific gravity, thermal conductivity and the physical dimension of the column cross section. Both of the temperature history versus time for the selected elements and the fire resistance has been analyzed using existing results. All the analyses have been carried out for the square cross-section under axial load 1380 kN.